Peran Masyarakat Desa Rejosari dalam Mencegah Stunting pada Anak - Nurul Kholillah; Sifana Nur Laila; M. Fauzul Adzim; Ainur Rofiah; Nanda Safitri; Octa Alfiani; Khoirun Nuha; Amelia Maharani; Akhriyadi Sofian (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
Stunting is a long-term nutritional problem that severely affects children's physical growth and cognitive development. To address stunting, Rejosari Village has developed various community-based initiatives. The purpose of this study is to find out how the Rejosari Village community functions to prevent stunting in children by using cooperation and participation strategies. Socialization of stunting, nutrition counseling for pregnant women and breastfeeding mothers, routine monitoring of pregnant women's health, and provision of supplementary food for children under five are some of the programs in which the community is actively involved. Village health cadres also play an important role in supporting the implementation of these programs by providing direct instruction and guidance to residents. A qualitative case study was conducted to collect data through field observations and interviews. The results showed that community involvement not only increased awareness of the importance of preventing stunting but also increased active participation in maintaining the health and nutrition of children in Rejosari Village. The village experienced a decrease in stunting rates due to strong community participation, which was supported by the village government and non-governmental organizations. The results suggest that the community-based intervention model used in Rejosari Village can be adapted and applied in other villages facing similar problems in preventing stunting.